Left Transforming into Right: The Adoption and Interpretation of the Ideas of the Fluxus Movement in Lithuania in the Second Half of the 20th Century - Zubavičiūtė, Dovilė (Lietuvos istorijos studijos, 2022)
The article examines how the ideas of the left-wing Fluxus movement were accepted and interpreted in Lithuania in the second half of the 20th century. The matter is that alongside unusual ways of artistic expression, the practices called fluxisms transcended the boundaries of the art field. The analysis has shown that the artistic actions and their content at that time, and especially in the 1980s and 1990s, were based on the quotation, adaptation, and use of Fluxus ideas in Lithuania. Freedom, experimentation, and performativity were intertwined with the political revival movement, the mood of national resistance, and the (self-)ironic relationship with the Soviet era. The ideas of the left avant-garde movement were understood and used for national cultural and political purposes during Lithuania’s revival.